2015
DOI: 10.14421/biomedich.2014.32.59-63
|View full text |Cite
|
Sign up to set email alerts
|

Substitution and Haplotype Diversity Analysis on The Partial Sequence of The Mitochondrial DNA Cyt b of Indonesian Swamp Buffalo (Bubalus bubalis)

Abstract: This research aims to investigate the substitution pattern of nucleotide base and haplotype diversity of Indonesian swamp buffalo (Bubalus bubalis) based on the mitochondrial DNA cyt b partial gene sequence. 17 samples were chosen from 7 different regions with each uniquely represents Indonesian biogeography which comprise Aceh, Riau, Madiun, Blitar, Lombok, South Borneo and Tana Toraja. The result of cyt b gene sequence alignment showed the presence of transition and transversion substitutions and the absence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 22 publications
1
9
1
Order By: Relevance
“…In the present study, it was found 856 (98.96%) conservation sites and 9 (1.04%) variable sites. Cyt b genes sequences of Indonesian swamp buffaloes in this study were more conservative than those reported by Sukri et al (2014) that found lower variable sites. The use of different Cyt b genes references from the GenBank influenced the results.…”
Section: Nucleotide Variationscontrasting
confidence: 89%
See 4 more Smart Citations
“…In the present study, it was found 856 (98.96%) conservation sites and 9 (1.04%) variable sites. Cyt b genes sequences of Indonesian swamp buffaloes in this study were more conservative than those reported by Sukri et al (2014) that found lower variable sites. The use of different Cyt b genes references from the GenBank influenced the results.…”
Section: Nucleotide Variationscontrasting
confidence: 89%
“…A total of 78 Cyt b genes sequences of local swamp buffaloes from 8 different populations were observed in this study. Previous studies reported that from 17 Cyt b gene sequences of Indonesian swamp buffaloes, 80.13% were found to be conserved sites and 19.87% were found to be variable sites (Sukri et al, 2014). In the present study, it was found 856 (98.96%) conservation sites and 9 (1.04%) variable sites.…”
Section: Nucleotide Variationssupporting
confidence: 51%
See 3 more Smart Citations